I. Dünya Savaşı’ndan Önce Türk Boğazlarına Yönelik Rus Talepleri ve İngiltere’nin Tutumu (1908-1914) - Abdurrahman BOZKURT (Gazi Akademik Bakış)
Taking advantage of the international developments, political crises and the situation of the Ottoman Empire prior the World War I, Russia raised its demands for the revision of the status quo of the Turkish Straits. At the first stage, the Russians were demanding that the Turkish Straits be opened to the warships of the states on the Black Sea coast. But the British opposed the status quo of the Straits to be revised, taking into account their national interests and possible changes in international relations in the future, even though they had been allies since 1907. During the Bosnian Crisis, when the Russians raised their demands for the Straits ‘ status quo to be revised, the British developed a formula to withdraw their allies’ demands. This formula, announced on 14 October 1908, was based on the acceptance of Russian demands on the condition that all states could enjoy the same rights. The Russians, who found the British counter-proposal to be against their interests, offered limited support during the Bosnian Crisis and the Tripoli War, and demanded that their demands be approved by the Ottoman Empire and even granted them the privilege of establishing a supply station in Istanbul. But the Ottoman statesman had enough political experience to know that these proposals were part of Russia’s plan to establish hegemony over the Straits region. Considering these proposals as a threat, the Ottoman statesmen first sought support from Britain. As Russia’s ally Britain remained neutral, the Ottoman Empire’s relations with Germany resulted in an alliance treaty. This study, based on published British archival documents, aims to examine Russia’s demands for revision of the status quo of the Turkish Straits between 1908-1914, but also the attitude of British and the developments behind the scenes by using official correspondence.